2016
DOI: 10.1177/1468017316653268
|View full text |Cite
|
Sign up to set email alerts
|

Adult social work and high-risk domestic violence cases

Abstract: SummaryThis article focuses on adult social work's response in England to high-risk domestic violence cases and the role of adult social workers in Multi-Agency Risk and Assessment Conferences. (MARACs). The research was undertaken between 2013-2014 and focused on one city in England and involved the research team attending MARACs, Interviews with 20 adult social workers, 24 MARAC attendees, 14 adult service users at time T1 (including follow up interviews after six months, T2), focus groups with IDVAs and Wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Neff et al, 2012), and that the majority had a Bachelor of Science in Social Work or a degree related to social sciences and health care. However, to be professional in vocational training, social workers need basic education as well as continuing training in an ongoing process (Flora & Argyroudi, 2016;Mclaughlin, Robbins, Bellamy, Banks, & Thackray, 2018). In this study the majority of the participants had participated in continuing education to a greater extent than found in similar studies (Danis, 2004;Dolunay-Cug, Toplu-Demirtaş, & Murray, 2017;Heffernan et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…Neff et al, 2012), and that the majority had a Bachelor of Science in Social Work or a degree related to social sciences and health care. However, to be professional in vocational training, social workers need basic education as well as continuing training in an ongoing process (Flora & Argyroudi, 2016;Mclaughlin, Robbins, Bellamy, Banks, & Thackray, 2018). In this study the majority of the participants had participated in continuing education to a greater extent than found in similar studies (Danis, 2004;Dolunay-Cug, Toplu-Demirtaş, & Murray, 2017;Heffernan et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, given some of the comments reported here, more work is needed on how the content and conduct of MARACs is affected when the police take the lead, something, which seems to have become more of a routine feature, as the move to digital online MARACs. It is difficult to assess the extent to which this leadership role enhanced the work of MARACs during the pandemic or inhibited the participation of other partners (on the importance of these issues in respect of attendance, McLaughlin et al, 2018)). The power and the function of the lead agency is an issue referred to by Bottoms (1990) and to a large extent remains unspoken.…”
Section: Conclusion: Limitations Of These Findings and Looking To The Futurementioning
confidence: 99%
“…The key purpose of a MARAC is, namely, information sharing, coordinated safety and action planning linking with other relevant agencies (McLaughlin et al, 2018). SafeLives goes on to say:…”
Section: Introductionmentioning
confidence: 99%
“…Whereas adult social care professionals can identify domestic abuse in older people, their knowledge of the pathways involved in tackling it can be limited (McLaughlin et al, 2016). Wydall et al (2015) found that in the 17 of the 21 local authorities consulted, adult social workers did not follow the domestic abuse pathway but went down the adult safeguarding route, irrespective of the individual needs of the older person.…”
Section: Recognising and Recording Domestic Abuse Of Older Peoplementioning
confidence: 99%
“…Research suggests that adult social workers are uncertain of their role in domestic violence cases and struggle to navigate between safeguarding and domestic abuse procedures operating in parallel (McLaughlin et al, 2016;Robbins et al, 2016). In Wales, Wydall et al (2015) report that agencies often work in silos, with little evidence of multi-agency working in the standard to medium risk cases.…”
Section: Integration Of Practicementioning
confidence: 99%